Coopération asynchrone en milieu médical : prise en compte de la gestion de la variabilité liée au patient dans la conception d’un outil de workflow - Maria Isabel Munoz; Flore Barcellini; Vanina Mollo; Adélaïde Nascimento (Activités)
The aim of this research is to characterize the practices of asynchronous cooperation implemented by radiographers in radiotherapy in order to guarantee the quality of this treatment. This study is a part of an industrial project to design a computerized tool supporting cooperative work (workflow tool) in radiotherapy. The methodology involves observation of the entire radiotherapy process and interviews with radiographers who work in the downstream and upstream phases of the treatment. The results describe the type and function of asynchronous cooperation practices used by radiographers to manage patient variability and to organise treatment sessions in order to guarantee quality of care. They open up perspectives concerning the consideration of asynchronous cooperation practices embedded in the design of collaborative tools in healthcare field.